Development of RT-qPCR assay for assessing the expression of ACTB and SDHA housekeeping genes in the cell cultures of mammalian hosts of zoonotic infections - N. A. Liapunova; M. A. Khasnatinov; G. A. Danchinova; I. S. Solovarov (Acta Biomedica Scientifica, 2024)
Background. The molecular mechanisms behind the maintenance of zoonotic pathogens in nature can be better understood by examining the gene expression in host cells in response to the infection. Reverse transcription and quantitative polymerase chain reaction (RT-qPCR) is a powerful method to study gene expression, especially with the use of endogenous reference genes (RG) to normalize the data. Therefore, it is critical to develop the reliable qRT-PCR assay and validate that selected RGs are stably expressed in the studied organism or cell culture.The aim. In this work, we aimed to develop the real-time qRT-PCR method for detecting mRNA of two candidate RGs, succinate dehydrogenase subunit A (SDHA) and beta-actin (ACTB), in the cell lines of mammalian hosts of zoonotic infections.Materials and methods. The SPEV (porcine embryonic kidney cell line) and ApnK (Korean field mouse kidney cell line) cells were grown in 24-well culture plates. Total RNA/DNA was isolated from trypsin-detached cell monolayers. Genomic DNA in the samples was removed with RNase-free DNase I, and one-step RT-qPCR was performed using primers for SDHA and ACTB gene fragments and the corresponding TaqMan hydrolysis probes. The experiment was performed in 4 independent replicates.Results. In the Korean field mouse cells, the linearity, efficiency, repeatability, and reproducibility of the RT-qPCR for ACTB gene mRNA corresponded to the modern requirements. However, RT-qPCR for SDHA exhibited good linearity and efficiency of the reaction, but CV values for repeatability and reproducibility slightly exceeded the recommended standards. In porcine cells, both assays had acceptable parameters. Thus, to use the SDHA as RG for ApnK cells, a detailed study of the stability of its expression in this particular model is required.Conclusions. New qRT-PCR assay was developed to assess the expression of housekeeping genes ACTB and SDHA in the cells of the Korean field mouse and domestic pig. Further research is necessary to validate these genes as references for quantitative assessment of gene expression in the cells of mammalian hosts of zoonotic infections.